Palaeozoological Collections (PZ), Swedish Museum of Natural History (NRM) - Kevin Holston (Swedish Museum of Natural History, 2015)
This dataset represents the physical and digital holdings of fossil animals at the Swedish Museum of Natural History. The collection includes more than one million items, including many type specimens. The main part of the collection consists of material from Sweden, mainly invertebrates from the lower Palaeozoic (Cambrian, Ordovician, Silurian), including extensive collections from the Silurian of Gotland. The collection also includes rich faunas, both invertebrates and vertebrates, from the Mesozoic of Scania. The non-Scandinavian invertebrate material also includes particularly important collections of microfossils from the early Cambrian, fossil seep faunas and material from the Arctic and Antarctic regions. The vertebrate collections include one of the world’s richest collections of Devonian fish, with a focus on Spitzbergen, Greenland, and Germany. There are also important holdings of South American Pleistocene mammals.
Keywords: Occurrence; Specimen; Animalia; Sweden; Antarctica; Worldwide; Gotland; Fossils; Occurrence; OCCURRENCE; Biological Sciences; Biologi